Redefining the gut as the motor of critical illness - Mittal, Rohit (2013)
The gut is hypothesized to play a central role in the progression of sepsis and multiple organ dysfunction syndrome. Critical illness alters gut integrity by increasing epithelial apoptosis and permeability and by decreasing epithelial proliferation and mucus integrity. Additionally, toxic gut-derived lymph induces distant organ injury. Although the endogenous microflora ordinarily exist in a symbiotic relationship with the gut epithelium, severe physiologic insults alter this relationship, leading to induction of virulence factors in the microbiome, which, in turn, can perpetuate or worsen critical illness. This review highlights newly discovered ways in which the gut acts as the motor that perpetuates the systemic inflammatory response in critical illness.